(untitled) (Proceedings of International Conference on Special Education, 2023)
This study explores the effect of using Fraction Funk Music (FFM) in teaching fractions to primary school students with special educational needs (SEN). Fractions are essential to the primary school curriculum, and a deep understanding of fractions is crucial for future mathematics learning. However, teaching fractions can be challenging, especially in inclusive classrooms, where students with SEN may have misconceptions about fractions. One common misconception is that fraction operations require only memorization of rules and procedures, leading to a superficial understanding of fractions. To address this issue, this study used a simple experimental design with ten Year 5 students with SEN from a school in Seremban, Negeri Sembilan. FFM, a teaching aid that incorporates music, was used to teach the addition of fractions to students. Pre- and post-tests were administered to measure the learning outcomes of the students. The results indicate that the use of FFM has led to a significant improvement in the student’s understanding of the addition of fractions. These findings suggest that the integration of music can be an effective tool for teaching the addition of fractions to students with SEN. The proposed improvements can guide future research on the use of music-based teaching aids for mathematics learning. Overall, this study emphasizes the importance of effective teaching strategies for students with SEN, especially in teaching fractions. FFM can be a valuable teaching aid to promote a deeper understanding of the addition of fractions, and teachers can incorporate music into their teaching to engage students with diverse learning needs. Further research can explore the effect of FFM on other mathematical concepts and diverse student populations.